(untitled) (Research, Society and Development, 2021)
Objective: To analyze the relationship between oral disease and the risk of developing hospital pneumonia, mediastinitis, endocarditis, surgical site infection and hospital death in patients undergoing elective cardiac surgery. Assess which risk factors would be related to the risk of nosocomial infection and death after cardiac surgery. Methodology: It was an analytical, observational, prospective study, carried out from January to December 2018. The study included 46 patients candidates for elective cardiac surgery and evaluated as to the type of heart disease, type of surgery, associated comorbidities, age, NYHA classification, BMI, ICU stay days, oral health assessment by a dental surgeon, occurrence of infection and hospital death. The analysis was done through analysis of absolute and relative frequencies, estimation of odds ratios, chi-square test and Mann-Whitney test. Results: Of the 46 patients analyzed, 11 (23.9%) of them had hospital infections and 4 (8.7%) died, there was no statistically significant difference in the variables studied with the occurrence of infection or death. The heterogeneity of the findings in the oral evaluation that ranged from edentulous patients with partial or total dentures, partial edentulous with or without prosthesis and varying degrees of oral disease that ranged from gingivitis, periodontitis to abscesses. The prostheses had varying degrees of conservation and hygiene. This great variability of findings may have implied no statistical significance in the variables. Conclusion: There was no statistical difference in the occurrence of hospital pneumonia, mediastinitis, endocarditis, surgical site infection and hospital death according to the patients’ oral health condition.